Nuclear Translocation and Activation of the Transcription Factor NFAT Is Blocked by Herpes Simplex Virus Infection - Scott, Emily S. (American Society for Microbiology, 2001)
Transcription factors of the NFAT (nuclear factor of activated T cells) family are expressed in most immune system cells and in a range of other cell types. Signaling through NFAT is implicated in the regulation of transcription for the immune response and other processes, including differentiation and apoptosis. NFAT normally resides in the cytoplasm, and a key aspect of the NFAT activation pathway is the regulation of its nuclear import by the Ca(2+)/calmodulin-dependent phosphatase calcineurin. In a cell line stably expressing green fluorescent protein (GFP)-NFAT, this import can be triggered by elevation of intracellular calcium and visualized in live cells. Here we show that the inducible nuclear import of GFP-NFAT is efficiently blocked at early stages of herpes simplex virus (HSV) infection. This is a specific effect, since we observed abundant nuclear accumulation of a test viral protein and no impediment to general nuclear localization signal-dependent nuclear import and retention in infected cells. We show that virus binding at the cell surface is not itself sufficient to inhibit the signaling that induces NFAT nuclear translocation. Since the block occurs following infection in the presence of phosphonoacetic acid but not cycloheximide, we infer that the entry of the virion and early gene transcription are required but the effect is independent of DNA replication or late virus gene expression. A consequence of the block to GFP-NFAT import is a reduction in NFAT-dependent transcriptional activation from the interleukin-2 promoter in infected cells. This HSV-mediated repression of the NFAT pathway may constitute an immune evasion strategy or subversion of other NFAT-dependent cellular processes to promote viral replication.